"Dual-gene" malaria-resistance: Therapeutically-rational exchange (T-REX) of group-O sickle trait and group-O C-traittrait red blood cells can be evaluated in Benin and Nigeria. (June 2020) - Jajosky, Ryan Philip; Jajosky, Audrey N.; Jajosky, Philip G.
Abstract: Background: Using indicators of disease severity, clinicians can predict which Plasmodium falciparum ( Pf ) malaria patients being treated with artesunate or quinine are likely to die despite these drugs. Effective "rescue adjuncts" are needed when drugs alone are inadequate. "Therapeutically-rational exchange" (T-REX) of special malaria-resistant red blood cells (RBCs) has been proposed to optimize adjunctive exchange transfusion. Methods: Studies were reviewed that (1) quantified how group-O status and "sickle-trait" (HbAS) and "C-trait" (HbAC) hemoglobins affect Pf mortality, risk of thrombosis, or birth outcomes for women with pregnancy associated malaria (PAM), (2) reported prevalences of "dual-gene" malaria-resistant RBCs, or (3) reflected the level of exchange-transfusion and malaria-related expertise in Benin and Nigeria. Results: Data show that the malaria- and thrombosis-resistance of RBCs depend on specific genes and the patient's clinical status and medical history. In malaria-endemic Benin and Nigeria, prevalences of "dual-gene" malaria-resistant group-O HbAS and group-O HbAC RBCs are substantial, and both malaria- and exchange-related expertise are outstanding. Conclusions: T-REX of "dual-gene" malaria-resistant RBCs is feasible in Benin and Nigeria and warrants evaluation as a rescue adjunct for 3 subsets of Pf -malaria patients. For therapeutic use, group-O HbAS RBCs are likely to be more effective than non-O HbAS RBCs for Pf -infected patients who (1) have a history of thrombosis or (2) are taking birth-control hormones while group-O HbAC RBCs may substantially improve birth outcomes for women with PAM. Studies suggest it is prudent to assume – until proven otherwise – that T-REX of "dual-gene" malaria-resistant RBCs can improve ("personalize") rescue of these patient subsets.